2006
DOI: 10.1016/j.jhazmat.2006.03.046
|View full text |Cite
|
Sign up to set email alerts
|

An on-line pre-concentration system for determination of cadmium in drinking water using FAAS

Abstract: In the present paper, a minicolumn of polyurethane foam loaded with 4-(2-pyridylazo)-resorcinol (PAR) is proposed as pre-concentration system for cadmium determination in drinking water samples by flame atomic absorption spectrometry. The optimization step was performed using two-level full factorial design and Doehlert matrix, involving the variables: sampling flow rate, elution concentration, buffer concentration and pH. Using the established experimental conditions in the optimization step of: pH 8.2, sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Some advantages of polymeric solid supports include low cost, simple preparation, high porosity and thus highly available surface area, and stability in acidic or basic media. Some polymeric solid supports such as amberlite XAD-2 [24,25], XAD-4 [26], polyurethane foam (PUF) [27][28][29], and grafted poly(tetrafluoroethylene) (PTFE) [30] have been used for preconcentration and determination of cadmium by FAAS. For a comparative study, the analytical merits data from some reported SPE methods for FAAS determination of cadmium are given in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Some advantages of polymeric solid supports include low cost, simple preparation, high porosity and thus highly available surface area, and stability in acidic or basic media. Some polymeric solid supports such as amberlite XAD-2 [24,25], XAD-4 [26], polyurethane foam (PUF) [27][28][29], and grafted poly(tetrafluoroethylene) (PTFE) [30] have been used for preconcentration and determination of cadmium by FAAS. For a comparative study, the analytical merits data from some reported SPE methods for FAAS determination of cadmium are given in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The chelating resins can be used in flow injection system with various detection methods like FAAS, ICP-AES, spectrophotometry, chemiluminescence and ICP-MS etc [26].There are various chelating resins have recently been used such as polyurethane foam [27][28][29][30][31][32][33][34][35], cellulose, silica gel [36][37][38][39][40][41][42], alumina [43][44][45][46][47][48], chitosan [49][50][51], carbon active [52] and polymeric resins like Amberlite etc. Amberlite XAD resins widely used to develop several chelating materials for preconcentration procedures due to its good physical and chemical properties such as porosity, high surface area, durability and purity.…”
Section: Applications Of Chelating Resins Based On Amberlite Xad mentioning
confidence: 99%
“…In recent years, several methods of preconcentration and separation of chromium(III) and chromium(VI) have been developed [9][10][11][12][13][14][15][16]. Instrumental analysis methods including atomic absorption spectrometry and inductively coupled plasma mass spectrometry always request previous steps of several separation-preconcentration procedures including solid phase extraction, ion exchange, cloud point extraction have been performed as separation technique [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%